2012
DOI: 10.4269/ajtmh.2012.11-0325
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Solar Water Disinfection Process (SODIS) Against Cryptosporidium parvum Using a 25-L Static Solar Reactor Fitted with a Compound Parabolic Collector (CPC)

Abstract: Abstract. Water samples of 0, 5, and 30 nephelometric turbidity units (NTU) spiked with Cryptosporidium parvum oocysts were exposed to natural sunlight using a 25-L static solar reactor fitted with a compound parabolic collector (CPC). The global oocyst viability was calculated by the evaluation of the inclusion/exclusion of the fluorogenic vital dye propidium iodide and the spontaneous excystation. After an exposure time of 8 hours, the global oocyst viabilities were 21.8 AE 3.1%, 31.3 AE 12.9%, and 45.0 AE 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…In contrast, Wilson demonstrated that there was no obvious trend between the presence of inorganic kaolin particles across a range of turbidity levels in water samples from 0–200 NTU and E .coli log reduction under various sunlight irradiances for 7 h [28]. In another recent research study by Fontán-Sainz et al ([2012]) using a solar CPC reactor, there was a significant loss of efficiency in the inactivation of Crytosporidium parvum oocysts under full sunlight conditions when the water turbidity increased from 5 to 30 NTU [46]. The study of Wilson [28] used a batch culture reactor whereas Fontán-Sainz et al [46] used an uncatalysed solar system for their disinfection treatment and these are both different methods compared to the present study using the continuous flow TFFBR system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Wilson demonstrated that there was no obvious trend between the presence of inorganic kaolin particles across a range of turbidity levels in water samples from 0–200 NTU and E .coli log reduction under various sunlight irradiances for 7 h [28]. In another recent research study by Fontán-Sainz et al ([2012]) using a solar CPC reactor, there was a significant loss of efficiency in the inactivation of Crytosporidium parvum oocysts under full sunlight conditions when the water turbidity increased from 5 to 30 NTU [46]. The study of Wilson [28] used a batch culture reactor whereas Fontán-Sainz et al [46] used an uncatalysed solar system for their disinfection treatment and these are both different methods compared to the present study using the continuous flow TFFBR system.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent research study by Fontán-Sainz et al ([2012]) using a solar CPC reactor, there was a significant loss of efficiency in the inactivation of Crytosporidium parvum oocysts under full sunlight conditions when the water turbidity increased from 5 to 30 NTU [46]. The study of Wilson [28] used a batch culture reactor whereas Fontán-Sainz et al [46] used an uncatalysed solar system for their disinfection treatment and these are both different methods compared to the present study using the continuous flow TFFBR system. The present study used a different TiO 2 reactor (immobilised form) and found a similar pattern of decreased microbial inactivation with increased turbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a 0.1 to 3 log 10 inactivation of C. parvum oocysts by solar inactivation. [11][12][13][14][15][16][17][18][19][20] This reported variation in inactivation efficiency could be attributed to the differences in the oocyst source, the UV transmission spectrum of reactor material, solution composition, temperature, and radiation spectrum used in these studies. The importance of solar spectrum was suggested by higher oocyst inactivation in UV transmitting containers such as borosilicate glass tubes 11,12,15,16 compared to plastic containers that block solar UV transmission.…”
Section: Introductionmentioning
confidence: 95%
“…Most of rural peoples in Ethiopia are not aware that SODIS is used as a HWT method [ 31 ]; whereas, over five million people in more than 50 developing countries disinfect their regular drinking-water by using SODIS [ 32 ]. Today, laboratory studies have consistently shown the efficiency of SODIS in significantly reducing the risk of a microbial contamination of drinking-water [ 33 , 34 ]. Though, an evidence-based health effect of SODIS intervention at the household level is limited, diarrheal disease problems could be prevented through improving the quality of drinking-water [ 35 ].…”
Section: Introductionmentioning
confidence: 99%